Dye-sensitized solar cell using local natural dye extract from Melastoma malabathricum L. fruit pulp - Iqbal, Mujahid (2016)
Solar energy generation become important today due to high energy demand since carbon based fuels contribute to green house that increase the global temperature. Therefore the third generation solar cell namely Dye-sensitized solar cells (DSSCs) have attracted considerable attention due to its advantages such as of low production cost, non-toxic material and simple fabrication process. The existing DSSC mainly implement synthetic dye in the fabrication process while some researcher utilizes natural dye from flowers and fruits for the environmental friendly synthesizer. However these dye are not available locally therefore this thesis focused on the study, fabrication and efficiency enhancement of dye sensitized solar cell based on local natural dye extract namely Melastoma Malabathricum. The fabrication process starts with the preparation of 2 pieces of FTO coated glass (2 × 2 cm2), cleaned and printed with TiO2 paste (1 × 1 cm2) and coated with Pt or Carbon or Graphite thin layer, respectively. The Both glass substrate are then annealed in furnace either in air or Argon gas at 450°C for 30 minutes. In the process, the TiO2 paste printing method has adopted the Screen Printing and Dr. Blade method. The coated glass is then soaked in Melastoma Malabathricum fruit pulp extract for 2 hours and then both glass are sandwiched and injected with electrolyte. The fabricated DSSC is evaluated using UV-Vis and light I-V to characterize the absorption and efficiency, respectively. From the experiment, The best efficiency result is 0.15%, with VOC of 0.568 V, ISC of 0.427 mA and FF of 0.626 has been attained, based on screen printing method and annealed in Argon gas while the efficiency of Blueberry dye based DSSC is only shows 0.079%.